Supporting Underserved Students How to Make PBIS Culturally and Linguistically Responsive (PBIS-Compatible Resources for Culturally and Linguistically Responsive Teaching). - Hollie, Sharroky (Solution Tree, 2022)
"Positive behavioral interventions and supports (PBIS) is, in theory, an effective method of creating equitable educational environments that serve all students. In practice, however, it often falls short, especially when concerning historically underserved students. There is a disconnect between cultural responsiveness and PBIS that creates a gap in PBIS effectiveness, often leaving Black and Brown students with disciplinary disproportionality and academic disparities. In Supporting Underserved Students: How to Make PBIS Culturally and Linguistically Responsive, Sharroky Hollie and Daniel Russell Jr. emphasize the need for alignment between PBIS and culturally and linguistically responsive teaching and learning to ensure equity for all students. They begin with an overview of traditional PBIS practices, highlighting where gaps exist for historically underserved students. Then they offer practical strategies for aligning, assessing, and activating culturally responsive practices for PBIS. The book also highlights situational appropriateness for cultural behaviors. It provides guidance on how teachers can validate and affirm students' cultural behaviors, and how they can build and bridge those behaviors to the academic and social skills students need in order to succeed at school and in mainstream society"--